The Effects of Classical Trapping on the Control of Malaria Transmission - Zhenbu Zhang; Tor A. Kwembe; Xing Yang (Journal of Basic & Applied Sciences, 2016)
This paper investigates the effects of classical trapping on the control of malaria transmission. The Ross-Macdonald model is modified and a trapping probability function is introduced to construct a partial differential equation (PDE) system. The proof of existence and uniqueness of solution of density functions to the PDE system is given, numerical simulation results based on Gaussian distribution and exponential distribution are obtained for the solutions, and graphical representations of solutions are shown and interpreted.